A Monte Carlo study of contraband detection using fast neutron resonance technique - Jinhyoung Bae; Jooho Whang (Functional Materials, 2004)
Fast neutron resonance technique was simulated using MCNP-4B (Monte Carlo N-Parti-cle System) to find its usefulness to contraband inspection. By applying neutron techniques, elemental composition of the material in question can be characterized, by which existence of explosives or narcotics are recognized among many other stuffs being investigated. To obtain fast neutron flux, D(d,n)3He reaction was chosen and using a computer code, DROSG-2000, we produced the flux with variables of energy and neutron radiating angle. Neutron energy range of 2.25 to 5.25 MeV, which includes apparent resonance peaks for carbon, oxygen and nitrogen, was applied to the simulation. By moving around the neutron source, a set of a material to be investigated and neutron detector experiences neutrons in the form of narrow line beam with different energies as the angle to the neutron source changes. By positioning the set of the material and detector at several angles, we can obt ain the equal number of linear equations to solve as the number of applied angles. Total attenuation of neutron flux obtained at different angles was calculated by using the resul ts of MCNP-4B simulation cases. Among many trials with different number of energy range segmentations and number of element in the material in question, feasible results could be found when the number of elements was five and energy bin was five to nine. More cases when the material in question was mixed or covered with interfering elements such as Al, Ni, Cr, Mn, Fe and Si were also simulated to show the increase of relative error up to 50 %. More studies to decrease the size of error occurring when the material in question exists wi th interfering elements and the effects of applying broad beam to the system are required. Способ резонанса быстрых нейтронов смоделирован с применением системы Монте-Карло MCNP-4B с целью определения его полезности для обнаружения контрабанды. Применение нейтронной техники позволяет охарактеризовать элементный состав исследуемого материала, откуда можно обнаружить наличие взрывчатых веществ или наркотиков среди множества других исследуемых веществ. Для получения потока быстрых нейтронов была выбрана реакция D(d,n)3He, и, используя компьютерный код DROSG-2000, мы моделировали такой поток с варьированием энергии и угла расхождения нейтронов. При моделировании использовался диапазон энергии нейтронов от 2,25 до 5,25 МэВ, в пределах которого возникают явные резонансные пики углерода, кислорода и азота. При перемещении совокупности образца исследуемого материала и детектора нейтронов вокруг источника нейтронов последние детектируются в виде узкого пучка с различной энергией, зависящей от угла поворота относительно источника нейтронов. Располагая совокупность образца исследуемого материала и детектора нейтронов под различными углами, можно получить число линейных уравнений, равное числу упомянутых углов. Полное затухание нейтронного потока, полученного при различных углах, рассчитано с использованием результатов моделирования по MCNP-4B. После множества проб с различными числами энергетических поддиапазонов и числами элементов в исследуемом материале правдоподобные результаты были получены для числа элементов 5 и числа энергетических поддиапазонов от 5 до 9. Моделированы также дополнительные случаи, когда исследуемый материал смешан или покрыт мешающими элементами, например, Al, Ni, Cr, Mn, Fe и Si, и показано, что при этом относительная погрешность возрастает до 50 %. Для снижения погрешности, возникающей при совместном присутствии мешающих элементов и исследуемого материала, и выяснения влияния применения широкого пучка необходимы дополнительные исследования. Cnocid резонансу швидких нейтронів змодельовано з застосуванням системи Монте-Карло MCNP-4B з метою визначення його корисності для виявлення контрабанди. Використання нейтронної техніки дозволяє охарактеризувати елементний склад досліджуваного матеріалу, звідки можна виявити присутність вибухових речовин або наркотиків серед багатьох інших досліджуваних речовин. Для одержання потоку швидких нейтронів було обрано реакцію D(d,n)3He, і, користуючись комп’ютерним кодом DROSG-2000, ми моделювали такий потік з варіюванням енергії та кута розходження нейтронів. При моделюванні застосовувався діапазон енергії нейтронів від 2,25 до 5,25 МеВ, в межах якого виникають явні резонансні піки вуглецю, кисню та азоту. При переміщенні сукупності зразка досліджуваного матеріалу та детектора нейтронів навколо джерела нейтронів останні детектуються у вигляді вузького пучка з різною енергією, що залежить від кута повороту відносно джерела нейтронов. Розташовуючи сукупність образца зразка досліджуваного матеріалу та детектора нейтронів під різними кутами, можна одержати число лінійних рівнянь, яке дорівнює числу згаданих кутів. Повне затухання нейтронного потоку, одержаного при різних кутах, розраховано з використанням результатів моделювання за MCNP-4B. Після численних проб з різними числами енергетичних піддіапазонів та числами елементів у досліджуваному матеріалі правдоподобні результати було одержано при числі елементів 5 і числі енергетичних піддіапазонів від 5 до 9. Модельовано також додаткові випадки, коли досліджуваний матеріал змішаний або покритий заважаючими елементами, наприклад, Al, Ni, Cr, Mn, Fe та Si, i показано, що при цьому відносна похибка зростає до 50 %. Для зниження похибки, яка виникає у спільній присутності заважаючих елементів та досліджуваного матеріалу, і з’ясування впливу застосування широкого пучка необхідні додаткові дослідження.